Pengembangan E-LKPD Berbasis Canva dalam Pembelajaran Pendidikan Pancasila Elemen Nilai-Nilai Pancasila Kelas IV Sekolah Dasar - Wahyuni Saputri; Reinita Reinita (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Rapid technological advances have contributed to a decrease in the effectiveness of education and eroded the values of nationalism and patriotism among the millennial generation. This study aims to design and develop Canva-based Learner Worksheets (LKPD) with a focus on Pancasila values material for grade IV students in Gugus 1, Padang Utara District. The approach used is Research and Development (R&D), with the application of the ADDIE model, namely Analysis, Design, Development, Implementation, and Evaluation. The E-LKPD that has been developed is then validated by experts using a questionnaire as a validation instrument. This validation involved experts in the fields of media, material, and language. The results of the validation showed that the validity level obtained was 97.5% for the media aspect, very valid category; 95% for the material aspect, very valid category; and 80% for the language aspect, which is still in the valid category. The final result of this validation process confirms that the Canva-based E-LKPD is very feasible and ready to be used in the learning process. In the pilot test at school, the teacher's response showed a percentage of 92.5%, while the students' response reached 89.8%, both in the highly valid category. The practicality test conducted at the research school showed that the teacher's response reached 97% and the students' response reached 93%, both also classified as very valid. Thus, it can be concluded that this Canva-based LKPD is very valid and effective to be applied as a learning tool in grade IV SD.